Guideline of Developing Community Capacity for Healthy City: A Case Study of Doi Phu Meun / แนวทางการพัฒนาศักยภาพชุมชนเพื่อให้เป็นชุมชนน่าอยู่: กรณีศึกษาดอยปู่หมื่น - Pongwiritthon / ภาคภูมิ ภัควิภาส และรัฐนันท์ พงศ์วิริทธิ์ธร, Pakphum Pakvipas and Ratthanan (Journal of Community Development Research (Humanities and Social Sciences); Vol 8 No 1 (2558): January - April 2015, 2015)
การวิจัยนี้เป็นการวิจัยเชิงปฏิบัติการเพื่อสร้างชุมชนแห่งการเรียนรู้ (Community Action Research: CAR) มีวัตถุประสงค์เพื่อพัฒนาศักยภาพของชุมชนดอยปู่หมื่นในการเป็นชุมชนน่าอยู่ โดยอาศัยแนวคิดทฤษฏีต่างๆ มาสร้างเป็นกรอบแนวคิดในการวิจัย ได้แก่ ศักยภาพของชุมชนการมีส่วนร่วมของชุมชน เมืองน่าอยู่ และการวิเคราะห์ชุมชนแบบมีส่วนร่วม โดยมีขั้นตอนการดำเนินงาน 3 ขั้นตอน คือ 1) การมองเป้าหมายร่วมกัน 2) การสร้างโครงสร้างและกลไกพื้นฐานเพื่อการพัฒนาชุมชนแห่งการเรียนรู้ 3) การกำหนดแผนโครงการร่วมกัน การเก็บข้อมูลโดยการสังเกตและบันทึกการดำเนินงานของชุมชน และสัมภาษณ์สมาชิกที่เข้าร่วมในกิจกรรม จากกลุ่มตัวอย่างที่มีส่วนได้ส่วนเสียของชุมชน จำนวน 50 ราย ได้แก่ ผู้นำชุมชน หัวหน้า และรองหัวหน้ากลุ่มอาชีพต่างๆ รวมถึงสมาชิกที่มีความสมัครใจ ในการเข้าร่วมโครงการ ผลการวิจัย พบว่า การดำเนินการพัฒนาศักยภาพชุมชนดอยปู่หมื่นให้เป็นชุมชนน่าอยู่ โดยสร้างชุมชนแห่ง การเรียนรู้ที่เปิดโอกาสให้ชุมชนมีส่วนร่วมในทุกกระบวนการผ่านการดำเนินงาน 3 ขั้นตอน คือ 1) การมองเป้าหมายร่วมกัน โดยการ จัดประชุมชาวบ้านเพื่อสร้างความเข้าใจที่ตรงกัน มีวิสัยทัศน์ และเป้าหมายที่ตรงกัน คือ พัฒนาชุมชนให้เป็นชุมชนน่าอยู่ และจัดกิจกรรมการสร้างวิสัยทัศน์และเป้าหมายร่วมกัน โดยผ่านกิจกรรมการประยุกต์ใช้กระบวนการวิเคราะห์ชุมชนแบบมีส่วนร่วม 2) การสร้างโครงสร้างและกลไกพื้นฐานเพื่อการพัฒนาชุมชนแห่งการเรียนรู้ โดยการเดินสำรวจเพื่อเก็บข้อมูล และจัดการประชุมเชิงปฏิบัติการเพื่อค้นหากลไกพื้นฐานในการพัฒนาให้เป็นชุมชนแห่งการเรียนรู้ 3) การทำโครงการร่วมกัน โดยจัดทำแผนปฏิบัติการเพื่อพัฒนาศักยภาพชุมชน ดอยปู่หมื่นให้เป็นชุมชนน่าอยู่ และมีการติดตามประเมินผลการดำเนินงานร่วมกันระหว่างผู้วิจัย ซึ่งกระบวนการดังกล่าวเกิดผลดีต่อชุมชนคือ การเกิดแนวคิดการมีส่วนร่วมของคนในชุมชน ทำให้ทุกฝ่ายที่เกี่ยวข้องเกิดกระบวนการคิด การทำงานอย่างเป็นระบบ มีความสามารถในการวิเคราะห์ปัญหาและความต้องการของชุมชน เกิดการยอมรับสภาพปัญหาในชุมชนและร่วมกันหาแนวทางแก้ไขปัญหาต่างๆ เกิดการเรียนรู้ในการวางแผนพัฒนาโครงการ การเขียนโครงการเพื่อของบประมาณหรือขอความช่วยเหลือจากองค์กรภายนอกต่างๆ และเกิดประสบการณ์ที่สามารถนำไปพัฒนาชุมชนในด้านอื่นๆ ต่อไปได้ ทำให้เกิดโครงการพัฒนาชุมชนดอยปู่หมื่นจากการบรูณาการ และการมีส่วนร่วมของชาวชุมชน เพื่อให้เป็นชุมชนน่าอยู่ คือ กินดี อยู่ดี มีคุณธรรม ตามหลักปรัชญาพอเพียง โดยมีโครงการที่จะนำไปสู่การพัฒนาชุมชน ได้แก่ 1) โครงการพัฒนาผลิตภัณฑ์ชา 2) โครงการจัดทำน้ำยาอเนกประสงค์ 4) โครงการพัฒนาหมู่บ้านตามหลักปรัชญาเศรษฐกิจพอเพียง 5) โครงการบูรณะวัดและโบสถ์ 6) โครงการฟื้นฟูศิลปวัฒนธรรมชนเผ่า   คำสำคัญ : แนวทางการพัฒนา  ศักยภาพชุมชน  ชุมชนน่าอยู่  การพัฒนาชุมชน   This research is an Action Research to create a Community of Practice (Community Action Research: CAR). The objective of the research is to develop the potential of Doi Pu Muen community to be a livable community based on the concepts and theories to create the framework of the research which are the potential of the communities, community’s participation, livable community, and Participatory Rural Appraisal (PRA). Three steps of the process are 1) to set up the Common Goal 2) to create the structures and mechanisms for the development of the Community of Practice 3) to set up the Common Action Plan. Data collected by  observing and recoding the operation of the community. As well as interviews with participating members and community stakeholders total 50 samples, including community leaders, chiefs and deputy chiefs of various professions and members who are willing to participate in the project. The results of the research showed that the operation of the potential development of communities for livable communities of Doi Pu Muen by created Community of Practice which gives the opportunities for the community to be able to participate in all three operation processes which are 1) to set up the Common Goal by created the villagers meeting to have the same understanding, same vision and same goal which is to develop the community to be livable communities and provide activities to create the same vision and Common Goal by the activities that apply from the Participatory Rural Appraisal. 2) To create the structures and mechanisms for the development of the Community of Practice by walked-through survey and workshop in order to find the fundamental mechanisms for the Community of Practice. 3) To set up the Common Action Plan by created the action plans to develop the potential development of Doi Pu Muen community to be livable communities and should also provide the processes of monitoring and evaluation between the researchers and community members. These processes are benefiting the community as it creates the concept of community participation, all parties involved in the thinking process, create the systematic working process, be able to work systematically way, be able to analyze the problems and needs of the community, acknowledge the problems of the community and work together to solve and find the solution of the problems as well as learn to plan the project development. The community leaders should be able to write the budget proposal or assistance from outside organizations and get the experiences that can be used to develop the community in the other aspects as well as creates Doi Pu Muen community development project from integration and involvement of the community members to create livable communities, which are well-being and live happily according to the philosophy of sufficiency economy. The project will contribute to the community development include 1) New tea product development project, 2) All-purpose cleaner making project, 3) Village development project under the philosophy of sufficiency economy, 4) Temple and church renovation project, 5) Tribal cultural regeneration project.   Keyword: Guideline of Development, Potential of Community, Livable Communities, Developing Community
Keywords: แนวทางการพัฒนา ศักยภาพชุมชน ชุมชนน่าอยู่ การพัฒนาชุมชน Guideline of Development, Potential of Community, Livable Communities, Developing Community